Macroeconomic Determinants of Renewable Electricity Technology Adoption in Thailand - Ungwanitban, Jidapa; Taj, Salah ud Din (iRASD Journal of Economics, 2020)
Renewable energy plays a significant role in mitigating C02 emission and boosts sustainable development. Initially, this study examines those factors which create hurdles in adopting renewable energy technology in Thailand. Later, this study examined the impact of renewable energy with other supporting variables on Thailand's total energy consumption. For this purpose, this study used 38 years of data from 1990 to 2018. Initially, the Augmented Dickey fuller test applied to verify the order of integration on indicators, and it confirms that there exists a unit order of integration. Then applied Johansen Cointegration, and it confirms that there are long-run relationships among trade openness, GDP, energy consumption (fossil fuels), financial development, and renewable energy consumption. Further applied Vector error correction model (VECM) to estimates the coefficients on indicators. Results confirm that openness to trade endorses the consumption of renewable energy in Thailand. However, the development of the economy and traditional energy resources creates hurdles to adapting renewable energy in Thailand. Renewable energy technology in Thailand did not significantly impact financial growth and development. After the research, the researcher advised the government of Thailand to adopt and implement the regulations and policies that maximize the magnitude of renewable energy and maximize the portion of renewable energy in total consumption of the overall energy consumption for the country Thailand.